2022
DOI: 10.3390/molecules27248707
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Sub-ppm CH3COOH Detection by Improved Assembly of Sn3O4-RGO Nanocomposite

Abstract: Detection of sub-ppm acetic acid (CH3COOH) is in demand for environmental gas monitoring. In this article, we propose a CH3COOH gas sensor based on Sn3O4 and reduced graphene oxide (RGO), where the assembly of Sn3O4-RGO nanocomposites is dependent on the synthesis method. Three nanocomposites prepared by three different synthesis methods are investigated. The optimum assembly is by hydrothermal reactions of Sn4+ salts and pre-reduced RGO (designated as RS nanocomposite). Raman spectra verified the fingerprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, they may encounter limitations related to sensitivity, selectivity, response time, susceptibility to environmental interference, and sensing material stability. To address these limitations, as elucidated in the Introduction paragraph, integrating graphene (RGO or G) with metals [32] or ceramics [33] has enabled chemiresistors to operate effectively at room temperature, achieving remarkable sensitivity with detection limits of up to 1 ppb [34].…”
Section: Sensing Electrical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may encounter limitations related to sensitivity, selectivity, response time, susceptibility to environmental interference, and sensing material stability. To address these limitations, as elucidated in the Introduction paragraph, integrating graphene (RGO or G) with metals [32] or ceramics [33] has enabled chemiresistors to operate effectively at room temperature, achieving remarkable sensitivity with detection limits of up to 1 ppb [34].…”
Section: Sensing Electrical Characterizationmentioning
confidence: 99%
“…Conversely, sensors based on GQDs-ZnO composites (GQDs: graphene quantum dots) could be operated at room temperature and exhibited a stronger response to acetic acid gas compared to a pure ZnO sensor, detecting up to 1 ppm at room temperature [30]. The mesoporosity of a metal oxide (CuO) was utilized to create a sensor operating at 200 • C [31], whereas the incorporation of graphene (RGO or G) in conjunction with metals [32] or ceramics [33] enabled chemiresistors to function at room temperature with exceptional sensitivity (achieving a limit of detection of up to 1 ppb [34]). Avossa et al (2018) reported that a chemiresistor based on ES nanofibers of a blend of polystyrene and polyhydroxybutyrate (PS-PHB) hosting MGC (0.93% mass ratio) was sensitive and selective to acetic acid vapors, but only worked at a temperature slightly higher than room temperature (T = 40 • C).…”
Section: Introductionmentioning
confidence: 99%